Analysis of Financial Performance Before and After the Implementation of PSAK 73 in the Mining Sector Listed on the Indonesia Stock Exchange - Hafiza, Tengku (Jurnal KIAFE, 2025)
This study aims to analyze the differences in financial performance before and after the implementation of PSAK 73 on leases in mining companies listed on the Indonesia Stock Exchange (IDX). This research employs a comparative descriptive method with a quantitative approach. The research sample consists of 30 mining companies selected using purposive sampling from companies listed on the IDX during the 2018–2021 period. The data used in this study are secondary data obtained from audited annual financial reports. Financial performance is measured using solvency ratios, namely Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), as well as profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE). Data analysis was conducted using descriptive statistical analysis, normality testing, and the Wilcoxon Signed Rank Test with the assistance of SPSS version 25. The results indicate that the implementation of PSAK 73 significantly affects financial performance measured by DAR and DER, as evidenced by significant differences before and after the implementation of PSAK 73. However, no significant differences are found in ROA and ROE after the implementation of PSAK 73. These findings indicate that the capitalization of lease transactions under PSAK 73 primarily affects the structure of liabilities and equity, while its impact on profitability performance remains limited.